2011
DOI: 10.1002/elan.201100171
|View full text |Cite
|
Sign up to set email alerts
|

A New Electrochemical Biosensor for Determination of Hydrogen Peroxide in Food Based on Well‐Dispersive Gold Nanoparticles on Graphene Oxide

Abstract: Herein, we describe a new method for the detection of hydrogen peroxide (H 2 O 2 ) in food by using an electrochemical biosensor. Initially, ultrafine gold nanoparticles dispersed on graphene oxide (AuNP-GO) were synthesized by the redox reaction between AuCl 4 À and GO, and thionine-catalase conjugates were then assembled onto the AuNP-GO surface on a glassy carbon electrode. With the aid of the AuNP-GO, the as-prepared biosensor exhibited good electrocatalytic efficiency toward the reduction of H 2 O 2 in pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…529 The was surface bound by conjugation of terminal amino groups of its lysine residues and the carboxyl groups on the Au NPs. 530 The glucose biosensor demonstrated good stability and efficiently measured the blood sugar concentrations in human serum.…”
Section: Biosensorsmentioning
confidence: 99%
“…529 The was surface bound by conjugation of terminal amino groups of its lysine residues and the carboxyl groups on the Au NPs. 530 The glucose biosensor demonstrated good stability and efficiently measured the blood sugar concentrations in human serum.…”
Section: Biosensorsmentioning
confidence: 99%
“…[3,4]. Therefore, the determination of H 2 O 2 concentration is of great importance in both biological and environmental systems.…”
Section: Introductionmentioning
confidence: 99%
“…The Joint FAO/WHO Expert Committee on Food Additives (JECFA) reported that ingesting small amounts of H 2 O 2 produced no toxicological effects because it could be decomposed quickly by enzymes in intestinal cells. [6] However, consumption of solutions with a H 2 O 2 content greater than 3% (household strength) can cause vomiting, mild mucosa irritation, and burns in the mouth, throat, oesophagus, and stomach. The ingestion of solutions with H 2 O 2 concentrations higher than 10% can cause more dangerous injury, such as mucosa burn.…”
Section: Introductionmentioning
confidence: 99%